Analisis Pendapatan Asli Desa Setelah Penetapan UU No 6 Tahun 2014 Tentang Desa - I Putu Fery Karyada (Universitas Pendidikan Ganesha, 2020)
This study analyzes the development of village income in Tabanan. The research subjects were 133 villages in 10 sub-districts with the object of village income in 2016, 2017 and 2018. Data were analyzed using a descriptive then presented using tables and graphs. The results revelaed villages in Pupuan and Penebel had a positive income, that is an increase in 2018. Whereas for the other sub-districts experiencing stagnation tends to decrease. One factor causing is the do not have strong economic base managed by the village government. Dana Desa cannot be managed properly to increase the village's income.